Nesting of bees on agricultural properties in the Santo Ângelo Microregion of Rio Grande do Sul state, Brazil - Rafael Narciso Meirelles; Luana de Fátima da Silva Ferreira; Dante Trindade de Ávila; Lauren Nathiely Garcia Uhlmann; Natália Ribeiro Antunes; Ariane dos Santos Guimarães (Agro@mbiente On-line, 2025)
Bees are major pollinators and play a key role in the reproduction of numerous plant species, thus ensuring the survival of many ecosystems. However, bee populations are currently in decline due to factors that negatively affect natural nesting habitats, which could ultimately lead to their disappearance. The expansion of agricultural land has significantly altered the landscape of the Santo Ângelo microregion in Rio Grande do Sul state (RS), Brazil. Thus, the aim of this study was to identify bee nesting sites and species on agricultural properties in the municipalities Santo Antônio das Missões, Rolador and São Luiz Gonzaga within the Santo Ângelo microregion. Nest surveys were conducted in trunks, soil, and manmade structures located near residential areas of the properties and in forest fragments adjacent to crops and pastures. Some specimens were collected, sacrificed, and taken to the laboratory for identification. Arboreal substrates were identified, and diameter at breast height (DBH) and nest entrance height (NEH) were measured. A total of 25 bee nests were identified: one in a dry trunk, five in masonry structures, and 19 in trees. The bees captured belonged to the genera Plebeia, Scaptotrigona, Tetragonisca, and Trigona, and were found in 12 tree species with a mean DBH of 0.65cm. The strongest bee-substrate associations were between T. angustula and T. fiebrigi in Handroanthus albus (4 nests), and T. angustula and T. fiebrigi in masonry structures (3 nests). The most frequently used trees were Handroanthus albus and Cordia americana, associated with Tetragonisca and Plebeia. The results highlight the importance of preserving forested areas near crops and pastures and maintaining tree species that favor bee nesting.